Flu fallout: information production constraints and corporate disclosure - CHEN, Chen. (Institutional Knowledge at Singapore Management University, 2023)
Using influenza epidemic data, we examine how constraints on corporate information production affect disclosure policies. We find that firms in areas with higher flu activity are less likely to issue short-run earnings forecasts and more likely to issue long-run earnings forecasts. These results are more pronounced when the information production process is more complex, when managers face a greater reputational loss for issuing low-quality short-run forecasts, and when firms’ costs of switching the forecast horizon are lower. Further analysis implies that the effect of flu activity on these forecast issuance decisions is not driven by firm performance or information uncertainty. Our results suggest that managers do not simply avoid issuing forecasts in response to information production constraints. Instead, they shift the forecast horizon from short-run to long-run, appearing to balance the costs of issuing low-quality forecasts with those of not issuing forecasts at all.